ABOUT PHILOSOPHICAL BELIEF (American Journal of Research in Humanities and Social Sciences, 2023)
This article aims to justify the philosophical interpretation of the divine faith, or-the philosophies of the interpretation of phenomena in existence and the use of explanations-rules, that is, the assertion that what phenomenon is in existence "can be explained through approximately selected reasons and used within the framework of that phenomenon (as it is considered)."